Advanced oral HIV-associated Kaposi sarcoma with facial lymphoedoema as an indicator of poor prognosis - L. Feller; R. Essop; M.H. Motswaledi; R.A.G. Khammissa; J. Lemmer (South African Family Practice)
Rapidly progressive facial lymphoedoema that develops concurrently with or immediately after rapid enlargement of oral Kaposi sarcoma in human immunodeficiency virus (HIV) -seropositive persons forebodes death. Previously, we reported on three patients with HIV-associated Kaposi sarcoma who had not been exposed to highly active antiretroviral therapy (HAART) and had extensive oral HIV-associated Kaposi sarcoma and rapidly increasing facial lymphoedoema. They died within three weeks of developing facial lymphoedoema. We present a similar case of an HIV-seropositive patient with extensive oral Kaposi sarcoma and associated facial lymphoedoema. She died three weeks after developing facial lymphoedoema. In contrast to our other previously reported cases, this patient had been on HAART for three months before she died. In light of this, we implore medical colleagues to treat patients with oral HIV-associated Kaposi sarcoma with HAART during the early maculopapular stage of Kaposi sarcoma. If the oral Kaposi sarcoma does not respond, as would be evident by the regression or disappearance of the lesions, then systemic chemotherapy should be added promptly, in order to prevent or delay the development of extensive exophytic oral lesions with facial lymphoedoema. These appear to be indicative of a very poor prognosis.